Tinjauan Undang-Undang Ketenagakerjaan dan Hak Asasi Manusia Terhadap Pelanggaran Hak Istimewa Buruh Perempuan PT Aice - Rubianti, Vaganti Safa Sukma (Media Hukum Indonesia (MHI), 2024)
A worker is an individual who is within the working age range of 15 to 64 years old, is currently engaged in employment, actively seeking employment, and has the capability to do work tasks.The issue of ensuring labour rights necessitates increased government attention. The persistence of worker ignorance regarding their rights and the misconduct of profit-driven entrepreneurs pose ongoing challenges that are difficult to eliminate due to inadequate government oversight. The rights and responsibilities of workers are explicitly outlined in the employment contracts that are issued. The rights and duties outlined in the work agreement must be in compliance with legal rules, as agreed upon by both parties. Employers are required to satisfy certain rights for female workers, including menstruation leave, delivery, miscarriage, and nursing. Nevertheless, numerous instances of female workers' privileges being violated persist in reality. Discrimination against female workers remains prevalent, exemplified by instances such as pregnant women being compelled to work late into the night. Furthermore, workers' limited awareness of their reproductive protection rights continues to hinder their fulfilment. Labour rights pertaining to women.